Prehospital Oxygen Administration for Chest Pain Patients Decreases Significantly following Implementation of the 2010 AHA Guidelines. (2nd October 2014) - Carhart, Elliot; Salzman, Joshua G.
Abstract Objectives. The purpose of this study was to examine trends in oxygen administration following the 2010 American Heart Association guidelines recommendation to withhold oxygen therapy for patients with uncomplicated presentations of ACS whose SpO2 is 94% or higher. Methods. Following IRB review and approval, we performed a retrospective analysis of data obtained from FisdapTM, a national, clinical skills tracking system for paramedic students between June 2010 and December 2012. Inclusion criteria included: 1) student consent for research, 2) cardiac chest pain recorded as the chief complaint, and 3) SpO2 data available for review. O2 administration, route, and dose were abstracted, and the percent of patient encounters with oxygen administration was calculated for each year. Unadjusted logistic regression was used to determine if O2 administration rates changed significantly over the study period. Unadjusted logistic regression was also used to determine if there was a difference in the odds of receiving oxygen based on a patient's SpO2 value. Results. 10, 552 patient encounters by 2, 447 paramedic students from 195 paramedic programs representing 49 states were included for analysis. Prior to release of the new guidelines (2010), 71.9% (95% CI 69.8–74.0%) of patients with SpO2 ≥ 94% received supplemental O2. Rates of O2 administration were significantly lower in 2011 (64%; 95% CI 62.7–65.3%) and in 2012 (53.1%; 95% CI 51.5–54.7). The odds of a hemodynamically stable chest pain patient with SpO2 ≥ 94% receiving supplemental oxygen in 2011 were 1.4 times lower compared to patients in 2010 (95% CI 1.3–1.6). Similarly, the odds of patients in 2012 receiving supplemental oxygen were 2.3 times lower compared to patients in 2010 (95% CI 2.0–2.6). The odds of receiving supplemental oxygen decreased by 4% for each 1% increase in SpO2 beyond the 94% threshold (OR = 0.96; 95% CI 0.94–0.98). Conclusions. The prehospital administration of supplemental O2 decreased significantly following release of the 2010 updated guidelines; however, our data revealed that 50% of patients not meeting criteria for administration still received supplemental O2.